Development of optimum process parameters and a study of the effects of surface roughness on brazing of copper - Tuan Zahari, Tuan Zaharinie; Huda, Z.; Izuan, M.F.; Abd Shukor, Mohd Hamdi (Elsevier, 2015)
Brazing experiments on commercially-pure copper plates, using brazing filler metal (MBF-2005), are conducted at temperatures in the range of 650-750 degrees C for time-durations in the range of 5-15 min. Shear tests for braze-joints involved use of a universal testing machine. Based on the shear-test results, a new brazing cycle has been developed that corresponds to the greatest shear strength of the braze-joint. The brazing cycle has been performed under a controlled dry-argon atmosphere in a tube furnace. Microscopic observations were made by use of both optical and electron microscopes; whereas surface roughness measurements were made by using a TRIO Surface Roughness Tester. It is found that successful brazing and good wetting can be achieved by the least voids by using an average surface roughness (R-a, value) for the base material. (C) 2015 Elsevier B.V. All rights reserved.